Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Sure, let's solve the system of equations step-by-step.
We start with the given system of equations:
1. [tex]\(\frac{x-1}{2} = y - 1\)[/tex]
2. [tex]\(2x = \frac{y}{2} + 5\)[/tex]
Step 1: Simplify the first equation
[tex]\(\frac{x-1}{2} = y - 1\)[/tex]
Multiply both sides by 2 to clear the fraction:
[tex]\[ x - 1 = 2(y - 1) \][/tex]
[tex]\[ x - 1 = 2y - 2 \][/tex]
Rearrange to solve for [tex]\(x\)[/tex]:
[tex]\[ x = 2y - 1 + 1 \][/tex]
[tex]\[ x = 2y - 1 + 2 \][/tex]
[tex]\[ x = 2y - 1 \][/tex]
Step 2: Simplify the second equation
[tex]\(2x = \frac{y}{2} + 5\)[/tex]
Multiply both sides by 2 to clear the fraction:
[tex]\[ 4x = y + 10 \][/tex]
Rearrange to solve for [tex]\(y\)[/tex]:
[tex]\[ y = 4x - 10 \][/tex]
Step 3: Substitute [tex]\(y = 4x - 10\)[/tex] into the first equation
We already have [tex]\( x = 2y - 1\)[/tex]:
[tex]\[ x = 2(4x - 10) - 1 \][/tex]
[tex]\[ x = 8x - 20 - 1 \][/tex]
[tex]\[ x = 8x - 21 \][/tex]
Now, solve for [tex]\(x\)[/tex]:
[tex]\[ x - 8x = -21 \][/tex]
[tex]\[ -7x = -21 \][/tex]
[tex]\[ x = 3 \][/tex]
Step 4: Substitute [tex]\(x = 3\)[/tex] back into [tex]\(y = 4x - 10\)[/tex]
[tex]\[ y = 4(3) - 10 \][/tex]
[tex]\[ y = 12 - 10 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
We start with the given system of equations:
1. [tex]\(\frac{x-1}{2} = y - 1\)[/tex]
2. [tex]\(2x = \frac{y}{2} + 5\)[/tex]
Step 1: Simplify the first equation
[tex]\(\frac{x-1}{2} = y - 1\)[/tex]
Multiply both sides by 2 to clear the fraction:
[tex]\[ x - 1 = 2(y - 1) \][/tex]
[tex]\[ x - 1 = 2y - 2 \][/tex]
Rearrange to solve for [tex]\(x\)[/tex]:
[tex]\[ x = 2y - 1 + 1 \][/tex]
[tex]\[ x = 2y - 1 + 2 \][/tex]
[tex]\[ x = 2y - 1 \][/tex]
Step 2: Simplify the second equation
[tex]\(2x = \frac{y}{2} + 5\)[/tex]
Multiply both sides by 2 to clear the fraction:
[tex]\[ 4x = y + 10 \][/tex]
Rearrange to solve for [tex]\(y\)[/tex]:
[tex]\[ y = 4x - 10 \][/tex]
Step 3: Substitute [tex]\(y = 4x - 10\)[/tex] into the first equation
We already have [tex]\( x = 2y - 1\)[/tex]:
[tex]\[ x = 2(4x - 10) - 1 \][/tex]
[tex]\[ x = 8x - 20 - 1 \][/tex]
[tex]\[ x = 8x - 21 \][/tex]
Now, solve for [tex]\(x\)[/tex]:
[tex]\[ x - 8x = -21 \][/tex]
[tex]\[ -7x = -21 \][/tex]
[tex]\[ x = 3 \][/tex]
Step 4: Substitute [tex]\(x = 3\)[/tex] back into [tex]\(y = 4x - 10\)[/tex]
[tex]\[ y = 4(3) - 10 \][/tex]
[tex]\[ y = 12 - 10 \][/tex]
[tex]\[ y = 2 \][/tex]
Thus, the solution to the system of equations is:
[tex]\[ (x, y) = (3, 2) \][/tex]
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.